Effects of cognitive impairment and depressive symptoms on health‐related quality of life in community‐dwelling older adults: The mediating role of disability in the activities of daily living and the instrumental activities of daily living. (16th September 2022) - Liang, Yan; Yang, Yinghua; Yang, Tingting; Li, Mengying; Ruan, Ye; Jiang, Yihua; Huang, Yanyan; Wang, Ying
Abstract: The objective of this study was to estimate the joint effects of cognitive impairment and depressive symptoms on health‐related quality of life (HRQoL) and to explore the mediating role of disability among Chinese community‐dwelling older adults. A cross‐sectional study was conducted with 2525 community‐dwelling older adults aged ≥60 years and living in Shanghai, China in 2019. Participants were divided into four groups: (1) non‐depressed without dementia, (2) non‐depressed with probable MCI, (3) depressed without dementia and (4) depressed with probable mild cognitive impairment (MCI). HRQoL was assessed using the 36‐Item Short‐Form Health Survey. Cognitive impairment and depressive symptoms were evaluated with the AD8 and the Geriatric Depression Scale respectively. Activities of daily living (ADL) and instrumental activities of daily living (IADL) disability and other sociodemographic variables were also assessed. The results of this study showed that controlling for sociodemographic characteristics, significant differences in a physical component score (PCS) and a mental component score (MCS) of HRQoL were found across the four groups. Compared to those who were non‐depressed without dementia, older adults who were depressed with probable MCI reported the lowest level of PCS and MCS, followed by older adults who were depressed without dementia. Both ADL and IADL disabilities played mediating roles in the relationship between cognitive impairment and depressive symptoms and PCS. Based on this study, we suggest that the early detection and adequate management of depressive symptoms and cognitive status—as well as efforts to improve individuals' ability to manage their ADLs and IADLs—may help to maintain or improve their HRQoL.